Recent Advances in Spectrally Selective Daytime Radiative Cooling Materials - Xie, An‑Quan; Qiu, Hui; Jiang, Wangkai; Wang, Yu; Niu, Shichao; Zhang, Ke‑Qin; Ho, Ghim Wei; Wang, Xiao‑Qiao (Nano-Micro Letters, 2025)
Daytime radiative cooling is an eco-friendly and passive cooling technology that operates without external energy input. Materials designed for this purpose are engineered to possess high reflectivity in the solar spectrum and high emissivity within the atmospheric transmission window. Unlike broadband-emissive daytime radiative cooling materials, spectrally selective daytime radiative cooling (SSDRC) materials exhibit predominant mid-infrared emission in the atmospheric transmission window. This selective mid-infrared emission suppresses thermal radiation absorption beyond the atmospheric transmission window range, thereby improving the net cooling power of daytime radiative cooling. This review elucidates the fundamental characteristics of SSDRC materials, including their molecular structures, micro- and nanostructures, optical properties, and thermodynamic principles. It also provides a comprehensive overview of the design and fabrication of SSDRC materials in three typical forms, i.e., fibrous materials, membranes, and particle coatings, highlighting their respective cooling mechanisms and performance. Furthermore, the practical applications of SSDRC in personal thermal management, outdoor building cooling, and energy harvesting are summarized. Finally, the challenges and prospects are discussed to guide researchers in advancing SSDRC materials. Highlights: 1 This review comprehensively presents recent advancements in spectrally selective daytime radiative cooling (SSDRC) materials, focusing on their fundamental characteristics, primarily concerning their structures and properties. 2 The fabrication principles and corresponding operational mechanisms of several typical SSDRC materials are systematically introduced. 3 Based on the latest research, this review highlights the innovative applications in personal thermal management, outdoor building cooling, and energy harvesting, while also discussing the challenges and prospects for the future development of daytime radiative cooling.